Non-Clinical Factors Influencing Clinical Decision of Root Canal Treatment (RCT): A Survey of Patients Reasons for Avoiding RCT: Non-Clinical Factors Influencing Clinical Decision of RCT - Farid, Huma; Khan, Basimah; Saad Shinwari, Muhammad; Yasir, Ayesha (Pakistan Journal of Health Sciences, 2022)
Root canal treatment (RCT) has high success rate, still many patients are apprehensive of this procedure. Objective: To determine the frequency of patients’ avoiding RCT in endodontically treatable teeth and identify the reasons given by the patients to avoid RCT. Methods: This cross-sectional study was conducted at the department of operative dentistry at Margalla Institute of Health Sciences, Rawalpindi including patients who refused RCT in endodontically treatable teeth (n= 250). Patient’s demographics, tooth related variables and reason for not pursuing root canal treatment were recorded. Descriptive statistics and Chi-Square test were run to report sample characteristics with level of significance at ≤ 0.05. Results: Two hundred and fifty (250, 21.09%) out of 1185 patients advised for RCT refused the procedure. Majority of the participants were female (169, 67.6%). The mean age of the patients was 32.66 years (SD ± 12.313). The most common reason as reported by almost half of the patients (106, 43%) for avoiding RCT was “financial constraints” followed by a desire to take a “second opinion or advice” (46,18%). The majority of the male participants as compared to female participants refused RCT due to financial constraints with statistically significant association (p˂0.001). A reasonable number of female patients also identified “want second opinion/advice” as a reason for avoiding RCT(p˂0.001). Conclusions: The frequency of patients avoiding RCT in endodontically treatable teeth was 21.09%. Financial constraints followed by seeking a second opinion or advice were the most common reasons identified by the patients avoiding RCT in endodontically treatable teeth.